Raising Dairy Herd Replacements - Dhuyvetter, Kevin C.; Smith, John F.; Harner III, Joseph P.; Brouk, Micheal (My University, 2000)
This publication discusses the decision making factors for raising dairy herd replacements.
MF399_2000_10
Keywords: MF399; Economics; Livestock; MF